1994
DOI: 10.2172/10191446
|View full text |Cite
|
Sign up to set email alerts
|

Methodologies for estimating one-time hazardous waste generation for capacity generation for capacity assurance planning

Abstract: This report has been reproduced directly from the best available copy. Available to DOE and DOE contractors from the Office of Scientific and Technical Information, P. 0. Box 62, Oak Ridge, TN 37831; prices available from (615) 576-8401.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
1994
1994

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most one-time wastes are derived from the cleanup of Superfund sites, RCRA corrective action sites, and other contaminated sites. The EPA is generating a report 24 to understand this issue. At the time of this writing, an evaluation of this report indicated that much more work was needed regarding the methodology used to identify the impact of onetime waste generation on future capacity needs.…”
Section: Anticipated Demandmentioning
confidence: 99%
“…Most one-time wastes are derived from the cleanup of Superfund sites, RCRA corrective action sites, and other contaminated sites. The EPA is generating a report 24 to understand this issue. At the time of this writing, an evaluation of this report indicated that much more work was needed regarding the methodology used to identify the impact of onetime waste generation on future capacity needs.…”
Section: Anticipated Demandmentioning
confidence: 99%
“…The decision rules are expressed in terms of IF-THEN statements. The IF portion contains conditions for which a site would be evaluated; the THEN part indicates the fraction of the total volume of hazardous wastes moved off-site for treatment or disposal (see Tonn et al, 1993b). Three levels of estimates (high, medium, and low) are provided for each operable unit in the OFFCAP database.…”
Section: Decision Rules For Off-site Demandmentioning
confidence: 99%
“…Due to space limitations, only one is discussed here (ORNL methodology). For information on the other methodology based on EPA's "Regulatory Impact Analysis for the Final Rulemaking on Corrective Action for Solid Waste Management Units (RIA methodology)" (EPA, 1993a), see Tonn et al, 1993b. The methodology presented here builds on previous work by ORNL in its analysis of the costs of RCRA corrective action (Tonn et al, 1993a).…”
Section: Rcra Corrective Action Hazardous Waste Volumesmentioning
confidence: 99%